Aesthetic river index: a GIS-based multi-criteria framework for assessing visual quality in recreational urban rivers - Tallar, Robby Yussac; Mauregar, Golan Geldoffer; Suen, Jian-Ping (Frontiers in Built Environment, 2025)
Urban river systems play a vital role in balancing ecological health, recreational utility, and visual harmony in densely built environments. While numerous studies have assessed water quality and flood vulnerability, limited research has focused on the spatial quantification of aesthetic value in urban rivers. This study introduces a novel geographic information system (GIS)-based aesthetic river index (ARI) that integrates ecological [normalized difference vegetation index (NDVI)], physical [normalized difference turbidity index (NDTI)], and structural components through an analytical hierarchy process (AHP). The index was applied to three case study rivers with distinct urban characteristics: the Kalimas River (Indonesia), the Love River (Taiwan), and the Chao Phraya River (Thailand). Landsat 8 imagery and local land use data were processed to assess vegetation vigor and water clarity, while structural features were digitized and scored for visual impact. Results show that the Love River attained the highest ARI score due to its integrated landscape planning and high water transparency, while the Chao Phraya exhibited the greatest aesthetic diversity. Validation using field-based perception surveys yielded strong correlations (ρ > 0.68), affirming the ARI as a robust tool for riverfront planning. This methodology contributes a replicable framework for incorporating human-centric aesthetics into sustainable river management strategies.